Understanding of insurance technology from a consumers’ perspective: the antecedents of Malaysian millennials' acceptance on insurtech - Chang, Yik Khoon (2022)
Insurance technology (insurtech) refers to the application of various cutting edge technologies in providing insurance industry-specific solutions. Malaysian insurtech development is relatively slower as compared to the global rapid pace due to the incumbents’ scruple about consumers' insurtech acceptance. Not to mention, knowledge gap existed as studies of insurtech from consumers' perspectives are scarce. Concerning this, the Unified Theory of Acceptance and Use of Technology (UTAUT) framework is useful in predicting the factors of users’ technology acceptance, but it requires modification to enhance its applicability in different contexts. Against these backgrounds, this study aims to identify the consumers' perception of insurance and their acceptance of insurtech. Besides, this study aims to enhance the UTAUT model in the insurtech acceptance context by altering the relationship between variables, removing irrelevant variables as well as incorporating convenience, trust and regulatory expectancy into the research framework. Furthermore, this study also aims to identify the factors that influence consumers’ insurtech acceptance by using the modified UTAUT model. In-depth, this study focused on Malaysian Millennials as they are the digital nations that witnessed and grew with various cutting edge technologies. Also, they are the largest generation cohort with the highest purchasing power. By using the convenient sampling technique, 417 survey responses were collected for analysis. The findings indicated that the Malaysian Millennials expressed a positive attitude towards insurance and insurtech, despite their low awareness of insurtech. Moreover, the results asserted that performance expectancy, effort expectancy, facilitating conditions, convenience, trust and regulatory expectancy significantly influenced Malaysian Millennials’ insurtech acceptance. The results also indicated that the impacts of convenience, trust and regulatory expectancy on insurtech acceptance are stronger among females. The findings of this study have contributed some valuable insights and implications to the literature and practitioners regarding the understanding of insurtech from Malaysian Millennials’ perspective.